Baroreflex activation therapy with the Barostim™ device in patients with heart failure with reduced ejection fraction: a patient level meta‐analysis of randomized controlled trials. (3rd July 2022) - Coats, Andrew J.S.; Abraham, William T.; Zile, Michael R.; Lindenfeld, Joann A.; Weaver, Fred A.; Fudim, Marat; Bauersachs, Johann; Duval, Sue; Galle, Elizabeth; Zannad, Faiez
Abstract : Aims: Heart failure with reduced ejection fraction (HFrEF) remains associated with high morbidity and mortality, poor quality of life (QoL) and significant exercise limitation. Sympatho‐vagal imbalance has been shown to predict adverse prognosis and symptoms in HFrEF, yet it has not been specifically targeted by any guideline‐recommended device therapy to date. Barostim™, which directly addresses this imbalance, is the first Food and Drug Administration approved neuromodulation technology for HFrEF. We aimed to analyse all randomized trial evidence to evaluate the effect of baroreflex activation therapy (BAT) on heart failure symptoms, QoL and N‐terminal pro‐brain natriuretic peptide (NT‐proBNP) in HFrEF. Methods and results: An individual patient data (IPD) meta‐analysis was performed on all eligible trials that randomized HFrEF patients to BAT + guideline‐directed medical therapy (GDMT) or GDMT alone (open label). Endpoints included 6‐month changes in 6‐min hall walk (6MHW) distance, Minnesota Living With Heart Failure (MLWHF) QoL score, NT‐proBNP, and New York Heart Association (NYHA) class in all patients and three subgroups. A total of 554 randomized patients were included. In all patients, BAT provided significant improvement in 6MHW distance of 49 m (95% confidence interval [CI] 33, 64), MLWHF QoL of −13 points (95% CI −17, −10), and 3.4 higher odds of improving at least one NYHA class (95% CI 2.3, 4.9) when comparing from baseline to 6 months. These improvements were similar, or better, in patients who had baseline NT‐proBNP <1600 pg/ml, regardless of the cardiac resynchronization therapy indication status. Conclusion: An IPD meta‐analysis suggests that BAT improves exercise capacity, NYHA class, and QoL in HFrEF patients receiving GDMT. These clinically meaningful improvements were consistent across the range of patients studies. BAT was also associated with an improvement in NT‐proBNP in subjects with a lower baseline NT‐proBNP. Abstract : Picture of the Barostim device in‐situ and its mode of action along with summary effects in the meta‐analysis. 6MHW, 6‐min hall walk; CI, confidence interval; CRT, cardiac resynchronization therapy; MLWHF, Minnesota Living With Heart Failure; NT‐proBNP, N‐terminal pro‐brain natriuretic peptide; NYHA, New York Heart Association.